REPRESENTATION OF CULTURAL VALUES IN THE BESEMAH COMMUNITY OF PAGAR ALAM THROUGH THE REJUNG LITERARY ART TRADITION - Keryn Kania; Sumianto A Sayuti (RADJA PUBLIKA, 2026)
Indonesia has a wide variety of literary traditions that differ across each region, one of which is found in the Besemah Tribe in Pagaralam, South Sumatra. Rejung is a traditional art form that combines musical melodies and poetic verses as a form of cultural expression rich in meaning. This art form is an oral cultural heritage filled with symbolic values and social functions, especially within the context of traditional customs and culture. Through Rejung art, values such as honor, politeness, solidarity, and spirituality are transmitted from one generation to another. Therefore, the purpose of this study is to describe the cultural values contained in the Rejung art tradition of the Besemah community in Pagaralam, South Sumatra. The research method used is descriptive qualitative, while the data collection technique was conducted through literature studies using reliable sources such as journals, articles, undergraduate theses, dissertations, books, and other relevant references.